Modern reconstructions of mean and seasonal-scale climate from coastal marine gastropods (Turritellidae) - Scholz, Serena R.; Petersen, Sierra V.; Anderson, Brendan M. (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
Turritellid gastropods are aragonitic marine mollusks that are particularly abundant and widespread in the fossil record. With fast growth rates and a shallow coastal habitat, the oxygen isotopic composition of their shells has the potential to be an excellent recorder of ancient subannual climate variation. To date, tests of the reliability of oxygen isotope paleothermometry in this family of gastropods have been restricted to a few localities. We produce 15 new high-resolution oxygen isotope profiles of modern turritellid shells, and combine these with 28 other published profiles from a range of latitudes and locations in order to investigate generalizable relationships between shell δ18Ocarb and local climate data including temperature, precipitation, salinity, and δ18Osw. We find that turritellids accurately record mean SST values using existing temperature-δ18Ocarb relationships, but seasonal ranges in SST are frequently overestimated. Modern climate data from our study sites show correlations that can explain this overestimation through the following proposed mechanism: seasonal increases/decreases in rainfall lead to decreases/increases in local salinity and, by inference, δ18Osw, amplifying the seasonal signal in δ18Ocarb. We find that ignoring these seasonal variations in δ18Osw can significantly bias the calculation of seasonal temperature ranges from δ18Ocarb profiles derived from turritellids. Similar processes may also affect sclerochronological records from other nearshore, shallow-water marine calcifiers. •Turritellid gastropods can provide accurate estimates of mean annual SST.•Seasonal changes in local δ18Osw significantly bias estimates of seasonal SST ranges.•Turritellid δ18O profiles can inform local seasonality in hydrological cycle.